Emotional intelligence and frequency of alcohol use during adolescence - Calero, Alejandra Daniela (2019)
Introduction. Emotional intelligence has proven to be a relevant construct during adolescence and includes three components: attention to feelings, clarity of feelings, and mood repair. Within this age group, alcohol consumption is a central problem. Objective. The aim of this work is to study the relation between emotional intelligence and frequency of alcohol consumption in adolescents that attendant a high school from the Autonomous City of Buenos Aires, Argentina. Methodology. The TMMS-21 was administered to assess emotional intelligence, and an ad hoc questionnaire was administered to assess alcohol consumption. We performed comparisons between age groups and between genders, and we studied the predictive power of emotional intelligence through a lineal regression. Results. Attention to feelings was lower in those adolescents with frequent alcohol consumption. Moreover, results showed that attention to feelings was a predictor of alcohol consumption frequency in women, while age was a predictor of frequency of alcohol consumption for both genders. Conclusion. These findings suggest that alcohol consumption could function as a way of coping with the emotions that are not being attended to.